Le breton, langue-totem ? - Erwan Le Pipec (La Bretagne Linguistique, 2014)
Alongside the longstanding predictions of Breton’s imminent death, there have been continual announcements that it is undergoing a renaissance. At the time of writing, it is easy to identify many indicators of a high level of vitality, including institutional support from the regional authority, the inclusion of regional languages in the Constitution as part of France’s heritage, the use of Breton’s positive image by local producers, dynamic artistic creation in the region, the constant growth of bilingual education and the presence of Breton on the internet and social networks, which is producing a new type of activist. The aim of this article is to critically examine this new qualitative pro-Breton order. An investigation of the notions of dead language and living language leads to a proposal of the notion of totemic language for Breton. This notion is an intermediate category between the two and has a primarily identity-related function, which potentially opens up great prospects for it.